Nighttime Magnetic Perturbation Events Observed in Arctic Canada: 1. Survey and Statistical Analysis. Issue 9 (9th September 2019) - Engebretson, M. J.; Pilipenko, V. A.; Ahmed, L. Y.; Posch, J. L.; Steinmetz, E. S.; Moldwin, M. B.; Connors, M. G.; Weygand, J. M.; Mann, I. R.; Boteler, D. H.; Russell, C. T.; Vorobev, A. V.
Abstract: The rapid changes of magnetic fields associated with large, isolated magnetic perturbations with amplitudes |Δ B | of hundreds of nanotesla and 5‐ to 10‐min periods can induce bursts of geomagnetically induced currents that can harm technological systems. This paper presents statistical summaries of the characteristics of nightside magnetic perturbation events observed in Eastern Arctic Canada from 2014 through 2017 using data from stations that are part of four magnetometer arrays: MACCS, AUTUMNX, CANMOS, and CARISMA, covering a range of magnetic latitudes from 68 to 78°. Most but not all of the magnetic perturbation events were associated with substorms: roughly two thirds occurred between 5 and 30 min after onset. The association of intense nighttime magnetic perturbation events with magnetic storms was significantly reduced at latitudes above 73°, presumably above the nominal auroral oval. A superposed epoch study of 21 strong events at Cape Dorset showed that the largest |d B /d t | values appeared within an 275‐km radius that was associated with a region of shear between upward and downward field‐aligned currents. The statistical distributions of impulse amplitudes of both |Δ B | and |d B /d t | fit well the log‐normal distribution at all stations. The |Δ B | distributions are similar over the magnetic latitude range studied, but the kurtosis and skewness of the |d B /d t | distributions show a slight increase with latitude. Knowledge of the statistical characteristics of these events has enabled us to estimate the occurrence probability of extreme impulsive disturbances using the approximation of a log‐normal distribution. Key Points: Most intense events were associated with substorms; their association with magnetic storms was much lower above 73° MLAT Largest |d B /d t | values appeared within an 275‐km radius associated with a region of shear between upward and downward field‐aligned currents The statistical distributions of impulse amplitudes of both |Δ X | and |d X /d t | fit well the log‐normal distribution but varied with latitude